2016
DOI: 10.1007/s00253-016-7903-z
|View full text |Cite
|
Sign up to set email alerts
|

Techno-functional differentiation of two vitamin B12 producing Lactobacillus plantarum strains: an elucidation for diverse future use

Abstract: An appropriate selection of Lactobacillus strain (probiotic/starter/functional) on the basis of its techno-functional characteristics is required before developing a novel fermented functional food. We compared vitamin B (B, cobalamin) producing Lactobacillus plantarum isolates, BHM10 and BCF20, for functional (vitamin over-production, genomic insight to B structural genes, and probiotic attributes) and technological [milks (skim and soy) fermentation and B bio-fortification] characteristics. Addition of B pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 45 publications
0
23
1
Order By: Relevance
“…Production of vitamin B 12 has been shown to be limited to a few species of bacteria and archaea [27], and ensuring intake of adequate levels of this vitamin is a high concern with plant-based diets. In recent years, two strains of L. plantarum that produce vitamin B 12 have been isolated [28]. In the present study, the increase in vitamin B 12 in the fermentation treatments was less pronounced than that seen for riboflavin and folate.…”
Section: Resultscontrasting
confidence: 43%
See 1 more Smart Citation
“…Production of vitamin B 12 has been shown to be limited to a few species of bacteria and archaea [27], and ensuring intake of adequate levels of this vitamin is a high concern with plant-based diets. In recent years, two strains of L. plantarum that produce vitamin B 12 have been isolated [28]. In the present study, the increase in vitamin B 12 in the fermentation treatments was less pronounced than that seen for riboflavin and folate.…”
Section: Resultscontrasting
confidence: 43%
“…Considering that intake of 4 μg vitamin B 12 per day has been set as adequate by EFSA [29], it is clear that the fermented products evaluated in the present study could only provide a very small fraction of the total requirement, despite the significant increase. For the two vitamin B 12 -producing strains of L. plantarum previously isolated, it has been demonstrated that increased production of vitamin B 12 can be achieved by addition of a B 12 precursor such as 5aminolevulinate [28]. Thus, a future approach to increase the concentration of vitamin B 12 in fermented vegetables could be to ensure high concentrations of precursors before fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…An extensive set of genetic tools has been developed for LABs over the years and this can enable efficient metabolic engineering of industrially important strains. Efforts have been made to enhance production of vitamins like riboflavin (Burgess et al, 2004;Chen et al, 2017;Juarez Del Valle et al, 2017), folate (Albuquerque et al, 2017;Saubade et al, 2017;Meucci et al, 2018) and cobalamin (Bhushan et al, 2017;Li et al, 2017) in LAB and thereby increase the functional value of fermented food, but until very recently there were no reports on optimization of dairy production or metabolic engineering of LAB strains to achieve higher menaquinone levels. Several genomes of the dominating vitamin K2 producing LAB, L. lactis have been sequenced, and putative genes encoding the enzymes for the individual steps of menaquinone biosynthesis annotated (Wegmann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to P. freudenreichii (Van Wyk et al, 2011; Edelmann et al, 2016), also lactic acid bacteria like Lactobacillus reuteri (Santos et al, 2008; Molina et al, 2012; Gu et al, 2015) have been utilized in attempts to increase the vitamin B12 levels in food products through fermentation. While several Lactobacillus species, including L. reuteri (Taranto et al, 2003), L. plantarum (Bhushan et al, 2017), and L. rossiae (De Angelis et al, 2014), have been shown to produce vitamin B12-like compounds, their ability to produce active vitamin B12 in nutritionally relevant amounts remains to be shown. The reports of Lactobacillus studies utilizing methods capable of distinguishing between the different B12 forms are still rare and have revealed that only pseudovitamin B12 is produced (Santos et al, 2007; Crofts et al, 2013).…”
Section: Introductionmentioning
confidence: 99%